PELAKSANAAN SUPERVISI PENDIDIKAN OLEH KEPALA SEKOLAH MENUJU PENDIDIKAN BERMUTU DI SMP NEGERI 2 BANGKINANG KOTA - Rosmita Rosmita; Azhar Azhar; Murni Baheram (Universitas Riau, 2018)
The purpose of this study is to identify, analyze, and deseribe the implementationof supervise education by principal in junior high school 2 Bangkinang City, from the planningstage of supervision implementation, until the follow up plan of the supervision implementation.In this study, data and data sources will be taken through interview and observation methods.Interviews were conducted on the principal as key or key imformants, supervisor team orsenior teacher, vice principal, head administration, and subject teacher as control informants.Observation done by observing the process of supervison implementation of junior high school2 Bangkinang City. The results of the reseach indicate a good cooperation between the principaland the supervisor team and subjet teachers, because of the large number of teacher in juniorhigh school 2 Bangkinang City. The principal appoints senior teachers of each subject to assistthe principal’s work as a supervisor as well as an assesor. The planning of the supervision ofeducation by the principal with the supervisory team and the assessor has been so good bymaking the decision letter of the supervisor team and the assessor. The organization of principalsupervision involes the teacher with the supervision team to creatie a supervision schedule byentering into an agreement fist. The principal conducts classroom observation directly to seethe teaching and learning activities of subjet teachers. After the implementation of the principal’ssupervision a follow up plan.